Urban Morphology and the Social Potential of Space: A Form-Based Reading of the Saadi Informal Settlement, Iran - Nezhadmasoum, Sanaz; Vehbi, Beser Oktay (Mdpi, 2025)
Enhancing the social dimension of sustainability is essential for improving the livability of informal settlements, yet its evaluation is often constrained by the absence of reliable socio-economic data. This study addresses this challenge by demonstrating how a rigorous, form-based analysis can be utilized to interpret the social potential embedded within the physical structure of informal settlements. Focusing on the Saadi neighborhood in Shiraz, Iran, the research applies a validated four-part morphological framework-integrated with Space Syntax principles-to examine how specific spatial configurations create conditions supportive of social interaction and territorial security. Rather than attempting to measure social sustainability directly, the study conceptualizes physical morphology as a tangible proxy through which socially supportive spatial conditions can be inferred. The analysis reveals three critical morphological drivers: (1) a fine-grained urban fabric that directly enhances walkability and co-presence; (2) a low vertical profile that ensures visual permeability and informal surveillance; and (3) semi-private residential clusters that function as defensible space. These findings highlight how the physical form of informal settlements contains an underlying social logic that can be systematically decoded. The paper concludes that form-based analysis provides a replicable pathway for identifying the spatial scaffolding that supports community life, offering valuable insights for socially oriented upgrading strategies in data-scarce contexts.
Keywords: urban morphology; social sustainability; space syntax; form-based analysis; informal settlements; Saadi neighborhood; shiraz; Iran